KORELASI BIMBINGAN BELAJAR TERHADAP PRESTASI BELAJAR PADA SISWA KELAS VIII SMP NEGERI 12 PONTIANAK - Plasida, Yustina; M. Asrori, M. Asrori; Purwanti, Purwanti (Universitas Tanjungpura, 2023)
In the learning process, good learning methods are not born on groups of people, but skilss and training to have good learning patterns in everyday life. Tutoring is the conscious effort by educators to relate to ideals and desire changes in attitudes, behavior, knowledge growth, and personality for the better in order to achieve what students want in the classroom learning process. A guide given to guide students to make positive changes in their daily lives both at home and at school. The purpose of this study was to describe performance tutoring for grade VIII SMP Negeri 12 Pontianak students. The method used is the describe method. The study population was 147 and the sample consisted of 39 students from class VIII of SMP Negeri 12 Pontianak. Direct and indirect communication data collection techniques. Tools for colleting survey data and documents. The data analysis technique used the moment percent formula. As a result of.